(untitled) (Alternautas, 2022)
Quinoa farmers and new Peasantry in Bolivia Quinoa is currently integrated in global production networks, although this crop was almost completely unknown some decades ago. In Bolivia, prices of quinoa reached an all-time high in 2013 and 2014, which resulted in an important expansion of the agricultural frontier. This article discusses the impact of the quinoa boom through the lenses of the commoditisation debate. It examines practises and perceptions linked to land and labour, two elements that were coined out as “fictitious commodities” by Karl Polanyi. While Land cannot be sold in the region, because of its legal status, several elements point toward a commoditisation process. The findings also suggest that labour has been increasingly commoditised as well. Quinoa producers indeed tend to rely increasingly more on casual labour and the multiplication of productive assets in the area resulted in new forms of commoditised social relations.